Prostate cancer. Issue 10 (October 2016) - Pullar, Ben; Shah, Nimish
Abstract: Prostate cancer is the most common male cancer in the UK representing approximately a quarter of all male cancer diagnosis. The disease and treatment options are wide ranging from a relatively benign disease requiring monitoring only, to an aggressive malignancy requiring active treatment. This can prove a challenge to both the doctor and patient deciding on the best management option. Ongoing research is revolutionizing both the diagnostics and treatment of the disease. This article aims to summarize the current knowledge of prostate cancer and treatment options available.